OWNERSHIP STRUCTURE AND CORPORATE GOVERNANCE ON INVESTMENT EFFICIENCY - Ririh Anggraini Setyahety (UNIVERSITAS PGRI MADIUN, 2025)
The purpose of this study was to analyze the effect of ownership structure and governance on investment efficiency in mining companies listed on the Indonesia Stock Exchange for the period 2016-2023. The sampling technique used purposive sampling as many as 17 companies. The method used is a quantitative method with a panel data regression analysis tool with Fixed Effect Model and Random Effect Model approach. Based on the results of the study, it show that ownership concentration has a significant positive effect on investment efficiency, while managerial ownership and independent board of commissioners have no effect on investment efficiency. Keywords: Concentrated Ownership; Corporate Governance; Independent Board of Commissioners; Investment Efficiency; Managerial Ownership; Ownership Structure